Business internationalization inducing factors: The importance of knowledge and relational networks - Lobo, Carla Azevedo (2017)
Companies are currently required to continually innovate and restructure their operations in order to respond to the requirements of national and international competition. Companies have to find new ways to develop competitive advantages and acquire new skills, resources and capabilities. Based on the opinions of different factors considered as inducers of the internationalization process by companies that internationalized early in their life cycle. We developed an empirical study with 320 portuguese international firms and used the statistical software AMOS for a confirmatory factor analysis. We propose a Theoretical Model in accordance to Human Capital Theory, International New Ventures Theory, and the Population Ecology Approach. We find evidence of the importance of Networks, Specific Skills of its workers, International Experience of its workers and Entrepreneurial Propensity and to Take Risks from workers and top management team.